The Effects of Youth Labor Market Reforms: Evidence from Italian Apprenticeships - Andrea Albanese; Lorenzo Cappellari; Marco Leonardi (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper estimates the causal effects of the 2003 reform of the Italian apprenticeship contract which aimed at introducing the “dual system” in Italy by allowing on-the-job training. The reform also increased the age eligibility of the apprenticeship contract and introduced a minimum floor to apprentices' wages. Using administrative data and balancing techniques we find that five years after hiring, the new contract improves the chances of moving to a permanent job in the same firm, yet this happens mostly in large firms. There are also sizeable long-run wage effects of the reform, well beyond the legal duration of apprenticeships, compatible with increased human capital accumulation probably due to the training provisions of the reform.
Keywords: J24; J41; C21; 330; apprenticeship; permanent work; youth employment; covariate balancing propensity score